Justified. the complete second season [videorecording (DVD)] - Olyphant, Timothy; Searcy, Nick; Carter, Joelle; Pitts, Jacob; Leonard, Elmore, 1925-2013 (Culver City, Calif. : Sony Pictures Home Entertainment, 2012)
In season two, Raylan tangles with a ruthless Harlan County crime family, Winona finds herself in hot water after she is a victim in a bank robbery, Loretta begins to piece together what the Bennetts did with her father, and much more.